A NOVEL APPROACH FOR DETAIL SURVEYS BY THE MOTORIZED GPSSIT CONCEPT IN RESIDENTIALS AREAS AND ITS APPLICATION - KALAYCI, IBRAHIM; OGUTCU, SERMET (Boletim de Ciências Geodésicas, 2014)
This paper introduces the usage and reliability of Motorized GPSSIT technique which is a novel approach for surveying. It reviews the advantages of Motorized GPSSIT concept and also considers to provide GNSS accuracy in the process of surveying especially for the cases which cannot be surveyed directly by the satellite navigation systems (GPS-GNSS), such as closely packed residential areas, tall buildings, trees, etc., and also places which GNSS receivers cannot be work efficiently due to signal interferences. In this technique, all the survey instruments are installed on a bed of a pick-up truck whereas in present techniques they are installed on the ground, therefore it is called Motorized GPSSIT. Study area was chosen within the housing area of our campus. In this area, classical surveying, GPSSIT and Motorized GPSSIT were performed to collect data for comparison and for the analysis of this technique’s usability and reliability. Stop and Go and RTK surveying techniques were performed with GPSSIT and Motorized GPSSIT concepts. It is shown that the Motorized GPSSIT technique is applicable as other present techniques in terms of accuracy and reliability